Tantangan Dakwah Melalui Media Sosial di Era Media Baru - Anggit Pamungkas; Umi Halwati (ARKANA: Jurnal Komunikasi dan Media, 2023)
The Islamic values that are communicated through da'wah are values that can intersect with the times, and one of these times is the digital era. Entering the digital age is like diving into the roar of a flood of information; it can be disorienting and make it hard to make sense of the world around you. In today's digital age, da'wah needs to be flexible enough to meet the needs of a population increasingly interested in "mass culture." In light of this, "renewable" and humane preaching strategies and methods must be implemented. Renewable "da'wah" involves spreading one's message via the Internet. Preachers, as a result, need to hone their people skills and become proficient with technology to ensure that the da'wah they spread is cutting edge and applicable. This study employs a qualitative, descriptive methodology. Preachers, dais, and ustadz now have the option of using social media platforms like Twitter, Facebook, and Instagram to spread their message of da'wah in this modern era. The internet is instrumental in the da'wah process, and its use in a variety of new media platforms is evidence of this. As a result of this rapid development in science and technology, there is a great window of opportunity for preaching. Dakwah on the web will be a useful resource for uplifting, recalibrating, and reorienting people's lives.